"Bone Development" Is an Ontology Group Upregulated in Porcine Oocytes Before In Vitro Maturation: A Microarray Approach - Budna, Joanna; Bryja, Artur; Celichowski, Piotr; Kranc, Wiesława; Ciesiółka, Sylwia; Borys, Sylwia; Rybska, Marta; Kolecka-Bednarczyk, Agata; Jeseta, Michal; Bukowska, Dorota; Antosik, Paweł; Brüssow, Klaus P; et al. (DNA and cell biology, 2017)
Mammalian cumulus-oocyte complexes (COCs) reach full developmental capability during folliculogenesis and oogenesis. It is well recognized that only gametes achieving MII stage after in vivo or in vitro maturation (IVM) are successfully fertilized by a single spermatozoon. Although the process of oocyte nuclear and/or cytoplasmic maturation in pigs is well determined, there exist many differences that promote these processes in vivo and in vitro. Therefore, this study aimed to investigate the differences in RNA expression profiles between porcine oocytes before and after IVM using microarray and real-time quantitative polymerase chain reaction (RT-qPCR) assays. Experiments were performed on oocytes isolated from 55 pubertal crossbred Landrace gilts. The oocytes were analyzed both before and after IVM and only Brilliant Cresyl Blue (BCB)-positive gametes were used for subsequent microarray analysis (Affymetrix) and RT-qPCR analysis. The microarray assay, which measures expression of 12,258 transcripts, revealed 419 differentially expressed transcripts in porcine oocytes, from which 379 were downregulated and 40 were upregulated before IVM compared to those analyzed after IVM. After DAVID analysis, we found eight different transcripts, including IHH, BMP1, WWTR1, CHRDL1, KLF10, EIF2AK3, MMP14, and STC1. Their expression is related to the "bone development" ontology group and was further subjected to hierarchical clusterization. Using RT-qPCR analysis, we confirmed the results of the microarray assay, showing increased expression of the eight genes in oocytes before IVM compared to oocytes after maturation in vitro. It has been suggested that "bone development" belongs to one ontological group involving genes substantially upregulated in porcine oocytes before IVM. We suggest that the gamete mRNA expression profile before IVM may comprise stored transcripts, which are templates for protein biosynthesis following fertilization. We also hypothesize that these mRNAs may be a specific "fingerprint" of folliculogenesis and oogenesis in pigs.
Keywords: aktivace transkripce; prasata; down regulace; Bone Development; exprese genu; vývoj kostí; transkriptom; Gene Expression; RNA, Messenger; Swine; kvantitativní polymerázová řetězová reakce; oocyty; Up-Regulation; vývojová regulace genové exprese; oocytes; IVM techniky; Gene Expression Regulation, Developmental; Transcriptome; Transcriptional Activation; upregulace; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction; prekurzory RNA; Oligonucleotide Array Sequence Analysis; Gene Expression Profiling; oogeneze; RNA Precursors; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Animals; Down-Regulation; in vitro maturation; microarray; ženské pohlaví; zvířata; pig; In Vitro Oocyte Maturation Techniques; genová ontologie; Gene Ontology; Female; messenger RNA; Oogenesis; Oocytes